A Brief History of the Expert Witness. Issue 4 (December 2017) - Milroy, Christopher M.
Expert witnesses are now an accepted part of criminal and civil trials. The use of expert witnesses and the admissibility of their science has developed over the last 250 years, when the concept of allowing an expert witness to give opinion evidence on the facts of other witnesses was allowed by Lord Mansfield in the case of Folkes v. Chadd in 1782. This paper briefly describes how court procedures have changed over the centuries before opinion evidence was admitted and then traces the history of the expert witness in England, USA, and Canada, examining issues of admissibility and duties of the expert from the 18th century to the 21st century. The paper further describes the change in admissibility with US decisions in Frye and Daubert and how they have affected courts in the UK and Canada. Also described are recent decisions in the UK on duties of experts and immunity from suit.